Fostering EFL Learners' Speaking Fluency through Digital Storytelling: A Literature-Based Inquiry (Lembaga Pengembangan Kinerja Dosen, 2025)
This research-based investigation delves into the pedagogical affordances of digital storytelling (DST) as a vehicle for advancing students' speaking fluency in English as a Foreign Language (EFL). Informed by Vygotsky's Sociocultural Theory, namely the Zone of Proximal Development (ZPD) theory, the study positions DST not merely as a multimedia activity but as a culturally mediated learning aid promoting oral proficiency through socially situated practice. A synthesis of empirical studies published between 2005 and 2024 identifies that DST fosters rehearsal-based fluency acquisition, mitigates speech anxiety, facilitates learner autonomy, and enhances reflective language awareness. Further, DST facilitates peer interaction and self-regulation and thus initiates the sociocognitive processes necessary for fluent language use. However, ongoing challenges like unequal technology access, inconsistent assessment practice, and varying degrees of digital literacy hinder its full implementation. The study suggests that DST, when appropriately scaffolded and presented in relation to communicative syllabus goals, is an operational model for the development of speaking fluency in EFL contexts.